System engineering for IMS networks - Handa, Arun (Newnes/Elsevier, 2009)
The IP Multimedia Subsystem (IMS) is the foundation architecture for the next generation of mobile phones, wireless-enabled PDAs, PCs, and so on, delivering multimedia content (audio, video, text, etc.) over all types of networks. It is essential for network engineers/administrators and telecommunications engineers to not only understand IMS architecture but to also be able to apply it at every stage of the network design process. This book will contain pragmatic information on how to engineer IMS networks as well as an applications oriented approach, for engineering and networking professionals who are responsible for making IMS "play" in the real world. * Describes the convergence of wireless IMS (IP Multimedia Subsystem) with other networks, including wireline and cable. Discusses building interfaces for end users and IMS applications servers. Explores network management issues with IMS